Bauxite residue issues: IV. Old obstacles and new pathways for in situ residue bioremediation - Gräfe, M.; Klauber, Craig (Elsevier, 2011)
Worldwide bauxite residue disposal areas contain an estimated 2.7 billion tonnes of bauxite residue, increasing by ~ 120 million tpa. The future management of this residue is of increasing environmental concern. Ideally it would be utilized as an industrial by-product for other applications (the zero waste situation), but realistically the drivers for zero waste are not high and there are significant cost and liability barriers to implementation. Any future utilization will most likely be based on contemporary production and residue currently consigned to long-term storage is unlikely to be recovered, thus the environmental impact risk remains. This prompts the question as to whether remediation can be conducted in situ, i.e. changing the residue chemistry without specifically re-excavating for conventional processing. In this review the key parameters of residue chemistry and its physical properties are considered in the context of what is required for a remediated residue to support a viable eco-system, i.e. what is required for rehabilitation in terms of a series of easily understandable goals. Specifically residue characteristics of stable residue solution such that; pH of 5.5-9.0, sodium adsorption ratio (SAR) of = 7, exchangeable sodium percentage (ESP) of = 9.5, residual sodium carbonate (RSC) of = 1.25, electrical conductivity (EC) of < 4 mS/cm. These goals are a long way from typical existing residue. Bauxite residue itself is the by-product of an iconic hydrometallurgical process, namely the Bayer process. While understanding the hydrometallurgical consequences is one key to the successful implementation of a remediation strategy, it is also clear that the key to in situ remediation is most likely not conventional hydrometallurgy but a systematic and targeted bioremediation approach. The most promising pathway for an in situ rehabilitated bauxite residue disposal area would appear to be bioremediation based on strategies developed for saline-sodic soils using halophyte plants and alkaliphilic microbes to effectively farm sodium from the system and mitigate pH, respectively. On bauxite residue surfaces the advantages and similarities should closely parallel saline-sodic agricultural soils. Halophytes provide great potential to accomplish some of the necessary rehabilitation goals indicated. Practical environmental rehabilitation attempts to date have been more concerned with BRDA closure in a cosmetic sense. These have had some limited success and probably reflect the aim of the work to achieve re-vegetation, relying on a limited understanding of the residue chemistry and lacking detailed information on individual plant responses and tolerances. It is proposed that research design for bioremediation should commence with a more rigorous plant, fungi and microbe selection in conjunction with a better understanding of residue chemistry. That is, tackling both the abiotic and biotic aspects of the problem systematically, especially as the sodium halophyte farming would initially be progressing into an even more extreme environment. This cannot be an unassisted process; without intervention BRDA environments would remain sterile for an extended period of time. Amendments such as applied gypsum can further displace Na+ from the residue exchange complexes and in conjunction with other divalent cation strategies control pH within halophyte tolerance. Both halophyte produced organic acids and halophyte promoted microbial populations provide H+ and increase the partial pressure of CO2 in the rooting zones to further the rehabilitation process. Suitable drainage strategies, along with other additions (organic waste, sewage sludge, macro and micro-nutrients) will promote plant and microbe survival. Whilst this approach would not be envisaged to be either capital or operating intensive, it is not a "quick-fix". Bio-remediation is a process that would require multiple growing seasons, but well within the typical lifetime of a refinery operation. This is the final in a series of four related reviews examining bauxite residue issues in detail. © 2011 Elsevier B.V. All rights reserved.